Enhancing physiological psychological and time trial performance outcomes using tapering technique among junior cyclists - Hashim, Hairul Anuar (Pusat Pengajian Kesihatan, 2016)
The aim of this study was to investigate the effects of increased training loads during the final three days of taper using modified exponential taper on physiological, psychological and performance outcomes among junior cyclists. This study involved a pre- and postexperimental design with a control group and two experimental groups (modified exponential taper and normal exponential taper). Twenty one junior male cyclists were recruited and 19 subjects (Mean age = 16.95+ 0.8years) completed the whole study protocol. Participants were matched according to a baseline VChmax value and they were assigned into either normal exponential taper (NET), modified exponential taper (MET) and control groups (CON). Both experimental groups underwent three months of progressive endurance training followed by two weeks of taper, while the control group continued their endurance training until the end of the study period. All parameters were measured at baseline, pre-taper and post taper. The results of the Mixed Factorial Analysis of Variance (ANOVA) revealed significant interactions between experimental groups across the measurement sessions for maximum oxygen consumption (VChmax), maximum power output (Wmax), maximum heart rate (HRmax), rating perceive of exertion (RPE), hemoglobin (Hg), hematocrit (Het), lactate (Lac), creatine kinase (CK), lactate dehydrogenase (LDH), cortisol, fatigue and vigor. No significant interactions were observed for ferritin concentration value, anger, tension, depression and confusion scores. The results of post-hoc analysis revealed that both experimental groups (NET and MET) showed significantly higher values in VChmax, Wmax, RPE scores, Hg concentration values, Het concentration value and Lac concentration value and vigor scores compared to the control group. Furthermore, the results of post-hoc analysis showed that the experimental groups (NET and MET) had significantly lower HRmax, CK, LDH, cortisol concentration values and fatigue scores compared to the control group. The result also revealed that the experimental groups had significantly faster time in the 20 km time trial compared to control group at post taper. However, no significant differences were observed between the MET and NET groups. It is concluded that the MET and NET are equally effective in optimizing the physiological, psychological and performance outcomes among junior cyclists.